Marketing of Handicrafts: A Case Study of Andhra Pradesh State Handicrafts Development Corporation - Venkateswarlu, P. (Indian Journal of Marketing, 2004)
Handicrafts are an expression of the cultural ethos of a society. Indian Handicrafts have been symbols of the country’s unique culture and rich heritage. They are essentially products of old artistic skills embodying the creative imagination of a craftsman. Andhra Pradesh, an abode of aesthetic crafts, a cavern of culture, a haven of heritage excels in handicrafts, which bear a distinct stamp of unique beauty. The State has emerged as a potential source of many of the most unique products made in the country. The craftsmen in the State have carved a nitch for themselves in the hearts of people here and abroad. Arts and crafts in Andhra Pradesh reflect the innovative excellence of the craftsmen in all regional splendour, combining artistic appeal with utilitarian value.